PERUBAHAN BENTUK RUANG TERBUKA PUBLIK PADA BANGUNAN RUMAH SUSUN SARIJADI BANDUNG - Doddy Friestya; Shiulyana Shiulyana (TATANAN, 2007)
Abstract                Inadequacy and high price of urban land became so phenomenal lately. It caused the change of open public space into built area, so that the optimalization of open public space turns into maximalization. Open public space became one of the choices in building extension, caused by the need of space. This kind of phenomenon can be seen in flat complexes (Sarijadi Flat, Bandung, in particular), where there has been addition or alteration of the open public space function that differs from what it was originally constructed for. The density in flat which is affected by its inhabitant’s way of life along with their habits may lead to functioning adjacent spaces of their units as additional features. It also influenced to the physical form order of the flats to be ther irregular one. The pattern of open space utilization and function in the flat complex is also influenced by the condition, characteristic, society and inhabitant lifestyle and also horizontally social lifestyle which are dragged into vertical social lifestyle. The using of this kind of open public space has the tendency of inadvertent empty space filling, one that even the inhabitants are unaware of. It caused the transformation of the open public spaces into multifunctional built area such as the trading place, religious place, sport field, and gazebo. Key words: transformation, open space, multi storey public housing, Sarijadi Bandung Abstrak                Keterbatasan dan mahalnya harga lahan perkotaan yang sangat fenomenal saat ini mendorong teralihfungsikannya ruang terbuka publik menjadi area terbangun sehingga pengoptimalan berubah menjadi pemaksimalan ruang terbuka publik. Ruang terbuka publik menjadi salah satu pilihan dalam perluasan bangunan atas dasar kebutuhan akan ruang. Fenomena ini dapat ditemui pada komplek rumah susun (khususnya Rumah Susun Sarijadi, Bandung), dimana ada penambahan ataupun pengalihfungsian ruang terbuka publik sehingga bergeser dari fungsi awalnya. Kepadatan pada rumah susun terkait dengan pola kehidupan penghuni dengan kebiasaan-kebiasaannya mendorong pemanfaatan ruang yang berdekatan dengan unit hunian mereka sebagai fungsi tambahan unit hunian. Hal ini pada akhirnya juga mempengaruhi tatanan bentuk fisik rumah susun menjadi tidak beraturan. Pola penggunaan dan pemanfaatan ruang-ruang terbuka pada komplek rumah susun tidak terlepas dari kondisi, ciri khas,  pola hidup masyarakat dan penghuni rumah susun serta pola kehidupan sosial yang bersifat horisontal terbawa pada kehidupan sosial vertikal. Penggunaan ruang terbuka publik ini cenderung mengarah pada pengisian lahan-lahan kosong yang kurang terencana dan yang tidak diperhatikan oleh penghuni rumah susun itu sendiri (no man’s lands). Hal ini mengakibatkan berubahnya ruang terbuka publik menjadi lahan terbangun dengan berbagai fungsi, antara lain sebagai fungsi tempat berjualan, lapangann olahraga, dan gasebo. Kata Kunci: perubahan bentuk, ruang terbuka, rumah susun, Sarijadi Bandung